2010
DOI: 10.1037/a0018679
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of psychological assessment as a therapeutic intervention.

Abstract: This study entails the use of meta-analytic techniques to calculate and analyze 18 independent and 52 nonindependent effect sizes across 17 published studies of psychological assessment as a therapeutic intervention. In this sample of studies, which involves 1,496 participants, a significant overall Cohen's d effect size of 0.423 (95% CI [0.321, 0.525]) was found, whereby 66% of treatment group means fell above the control and comparison group means. When categorical variables were taken into account, signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
206
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(230 citation statements)
references
References 75 publications
13
206
0
6
Order By: Relevance
“…The importance of psychological assessment for both staff and clients has been highlighted in a meta-analysis of 17 studies (Poston & Hanson, 2010). The individual studies included in Finally, there are many commonalities between the factors associated with recovery and personal strengths and those related to resilience and post-traumatic growth.…”
Section: Psychological Assessmentmentioning
confidence: 99%
“…The importance of psychological assessment for both staff and clients has been highlighted in a meta-analysis of 17 studies (Poston & Hanson, 2010). The individual studies included in Finally, there are many commonalities between the factors associated with recovery and personal strengths and those related to resilience and post-traumatic growth.…”
Section: Psychological Assessmentmentioning
confidence: 99%
“…Furthermore, extant data indicate that the assessment process in this system is generally perceived as collaborative (Israel 2014). Collaborative assessment may improve the accuracy of data collected by enhancing trust between the assessor and the client, and has even been associated with modest positive treatment effects (Poston and Hanson 2010). On the other hand, there is some observed variation in the extent to which assessment data were collected collaboratively.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, Poston and Hanson (2010) highlight that psychological assessment itself can have a therapeutic intervention. Using meta-analytic techniques, they concluded that psychological assessment procedures -when combined with personalized, collaborative, and highly involving test feedback -have positive, clinically meaningful effects on treatment, especially regarding treatment processes.…”
Section: Discussionmentioning
confidence: 99%